ECO HARMONY: RECONCILING HUMANS AND NONHUMAN WORLDS IN LINDA HOGAN’S ONE CREATION - R. Sathya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Ecocritical poetry emerges as a potent tool for fostering environmental awareness. It embodies nature's profound influence, urging readers to embrace its transformative essence and seek comfort in its tranquil embrace. Linda Hogan, renowned as one of the foremost poets of nature, advocates for ecological harmony in her poem “One creation”. This poem is widely regarded as a plea for reconciliation between humanity and the nonhuman world. Through a close examination of "One Creation," the research elucidates Hogan's discourse on environmental justice, highlighting her commitment to safeguarding both the natural environment and humanity while advocating for ecological harmony. Grounded in the spirituality and traditions of Native Americans, Hogan's ecological viewpoint recognizes the inherent spiritual essence of all species, emphasizing the interconnectedness of humans and nonhumans in the quest for environmental preservation and sustainability.